O ESTÁGIO DE DOCÊNCIA NO SERVIÇO SOCIAL: ALGUMAS REFLEXÕES ENTRE A SUA IMPORTÂNCIA E OS DESAFIOS DA FORMAÇÃO - Sánchez Alvarado, Mariangel; da Silva Torres, Maria Adriana; dos Santos, Carla Janaina (Revista Serviço Social em Perspectiva, 2020)
The teaching practice as a part of graduate programs is a task that requires a systematic knowledge approach and a reflection that articulates several dimensions of the academic formation process. Thus, the practice modality performed at this level aims to lead the graduate student to insert themselves into the academic reality through a constant approach to the daily activities of teaching. Therefore, it provides with greater experience in the teaching, research and training areas, allowing the student to be more able to act as a future teacher after completing their sensu stricto academic training. First, we will approach the context of graduate programs, then the teaching practice in graduate programs, after that we will mention the contributions of social work and national regulations that support training in this area. Next, the pedagogical aspects of the practicing as professional training will be analyzed and we will reflect on points to be considered in this pedagogical process, in order to understand the meanings, challenges and propositions that guide this learning space and also critical training.